Antifouling properties of green seaweed Halimeda opuntia from the Coast of Aceh, Indonesia: Sifat antifouling Halimeda opuntia dari Pesisir Aceh, Indonesia - Gazali, Mohamad; Ismail, Noraznawati; Saidin, Jasnizat; Bakar, Kamariah; Siong, Julius Yong Fu (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Marine biofouling remains a critical challenge in the maritime sector, prompting researchers to explore sustainable, eco-friendly, and antifouling solutions derived from marine organisms. This study aimed to determine the optimal concentration of H. opuntia extract for effective antifouling activity. The research methods included antibiofilm, cytotoxicity, antibacterial, anti-quorum sensing assays, and in situ tests. The results revealed that the methanol extracts of H. opuntia exhibited significantly higher antibiofilm activity, with an IC50 value of 0.020 mg/mL. Cytotoxicity assays demonstrated the lowest toxicity against the L6 cell line, with an IC50 value of 70.79 µg/mL. Mechanistically, the H. opuntia methanol extract did not exhibit a bactericidal effect against Pseudomonas aeruginosa but blocked bacterial communication mechanisms through quorum quenching activity, as evidenced by the formation of colorless opaque zones in reporter assays. In situ trials were conducted in the waters of Redang Island and Kuala Kemaman, Malaysia. Panels coated with H. opuntia 5% extract demonstrated superior antifouling performance over three months, with fouling coverage rates of 11.19% and 9.10%, respectively. Further research is needed on the antifouling properties of H. opuntia to identify its active compounds, evaluate its long-term effectiveness, and determine whether it is cost-efficient for mass production.